PENGEMBANGAN MEDIA VIDEO TUTORIAL PENATAAN SANGGUL KEPANG PADA SISWA KELAS XI TATA KECANTIKAN KULIT DAN RAMBUT SMK NEGERI 8 MEDAN - Laurentriana Gea, Sesilia; Sitompul, Astrid; Pebri Annisa Damanik; Gracede Christina Hutagalung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a video tutorial learning medium and determine itsfeasibility for the braided bun styling unit at SMK Negeri 8 Medan. The study wasmotivated by students' difficulties in performing practical bun styling specificallybraided buns (Braided Backmess) including sectioning hair strands, achievingsufficiently dense teasing (backcombing), constructing the bun, creating braids, andrecalling procedural steps. The study employed the Research and Development(R&D) method using the ADDIE development model (Analysis, Design,Development, Implementation, and Evaluation) with 34 students as researchsubjects. Feasibility testing was conducted by three subject matter experts and threemedia experts. Data collection involved questionnaires regarding teacher andstudent needs, expert validation, and trials with small, medium, and large groups;the data were analyzed using descriptive quantitative methods. The results indicatethe successful development of a video tutorial medium, with subject matter expertvalidation scoring 95.62% ("Highly Valid") and media expert validation scoring90.95% ("Highly Valid"). Regarding media feasibility, the small-group trial scored90.42% ("Highly Feasible"), the medium-group trial scored 91.42% ("HighlyFeasible"), and the large-group trial scored 94.80% ("Highly Feasible"). Thus, theresearch data demonstrate that the developed braided bun styling video tutorial ishighly suitable for use in the braided bun styling unit for Grade XI students in theSkin and Hair Beauty program at SMK Negeri 8 Medan.